Pomalidomide, dexamethasone, and daratumumab immediately after lenalidomide-based treatment in patients with multiple myeloma: updated efficacy, safety, and health-related quality of life results from the phase 2 MM-014 trial. Issue 6 (12th May 2022) - Bahlis, Nizar J.; Siegel, David S.; Schiller, Gary J.; Samaras, Christy; Sebag, Michael; Berdeja, Jesus; Ganguly, Siddhartha; Matous, Jeffrey; Song, Kevin; Seet, Christopher S.; Acosta-Rivera, Mirelis; Bar, Michael; et al.
Abstract: Patients with relapsed/refractory multiple myeloma (RRMM) need proven subsequent therapies after early-line lenalidomide treatment failure. The phase 2 MM-014 trial (NCT01946477) investigated pomalidomide, dexamethasone, and daratumumab after 1 to 2 prior treatment lines (62.5%, 1 prior line) in patients with RRMM and prior lenalidomide (75.0%, lenalidomide refractory). With a median follow-up of 28.4 months, overall response rate was 77.7% (52.7% achieved very good partial response or better) and median progression-free survival was 30.8 months. For patients with lenalidomide-refractory disease, these outcomes were 76.2%, 47.6%, and 23.7 months, respectively. No new safety signals were observed; 64.3% experienced grade 3/4 neutropenia. Health-related quality of life was preserved or trended toward improvement through 12 treatment cycles. Pomalidomide, dexamethasone, and daratumumab given immediately after early-line lenalidomide-based treatment continues to demonstrate safety and efficacy, supporting pomalidomide-dexamethasone as a foundation of combination therapy in RRMM and providing evidence that the immunomodulatory agent class delivers benefit after lenalidomide treatment failure.